The Role of Psycholinguistics in Language Learning and Teaching - norita purba (Tell : Teaching of English Language and Literature Journal, 2018)
Psycholinguistics has provided numerous theories that explain how a person acquires a language, produces and perceives both spoken and written language. The theories have been used in the field of language teaching. Some experts use them as the basic theories in developing language teaching methods. It is known as psycholinguistics approach. Psycholinguistic approach views learning as a cognitive individual process happening within the individual and then moves to the social dimension. As an approach, there are some methods which were developed based on psycholinguistics theories such as natural method, total physical response method, and suggestopedia method. These methods apply psycholinguistic principles that how a person acquires his/her mother tongue or first language (First Language Acquisition), learns his/her second or third language (Second Language Learning), perceives a language (Language Perception), and produces language (Language Production). Language perception refers to listening and reading, while the language production refers to speaking and writing. Listening, reading, speaking and writing are called as the four of language skills. Specifically, psycholinguistics helps to understand the difficulties of these four skills both intrinsic difficulties and extrinsic difficulties. Psycholinguistics also helps to explain the errors students do in the language learning. Moreover psycholinguistics also defines some kinds of brain disorders that affect language learning performance such as agraphia and aphasia which must be treated properly. Psycholinguistics mainly helps teachers to consider the use of appropriate method to teach that four language skill.